Lobular Panniculitic Infiltrates With Overlapping Histopathologic Features of Lupus Panniculitis (Lupus Profundus) and Subcutaneous T-cell Lymphoma. (February 2015) - Bosisio, Francesca; Boi, Sebastiana; Caputo, Valentina; Chiarelli, Concetta; Oliver, Fergus; Ricci, Roberto; Cerroni, Lorenzo
<x xml:space="preserve">Abstract</x> Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is characterized by panniculitic infiltrates that may be difficult to distinguish from inflammatory disorders, particularly lupus erythematosus profundus (LEP). We report on 11 patients (M:F=5:6; median age: 49 y; range: 20 to 75 y) presenting with lobular panniculitic infiltrates showing histopathologic features of both SPTCL and LEP in different parts of the same biopsy specimen. The areas showing aspects of SPTCL revealed dense infiltrates of small and medium-sized, atypical α/β T-cytotoxic lymphocytes with focal rimming of the adipocytes and high proliferation. In other areas the infiltrate was composed of nodules of B lymphocytes arranged characteristically at the periphery of the fat lobules and in the septa and showing a low proliferation rate. CD123-positive plasmocytoid dendritic cells arranged in small clusters could be observed in 3 cases. Our observation raises an important question concerning the relationship between SPTCL and LEP. A simple chance overlap of 2 unrelated pathologies seems unlikely, as we could observe these unusual features in 11 cases, much more than mere chance would justify. Three other hypotheses may explain the features observed in our patients: (1) these are examples of SPTCL with focal histologic features mimicking those of LEP; (2) these are examples of LEP with focal atypical histologic features mimicking those of SPTCL; (3) SPTCL and LEP may represent 2 ends of a spectrum, a hypothesis that may be supported by the frequent association of the 2 diseases.